Four Approaches to Daodejing Translations and Their Characteristics in Korean after Liberation from Japan - Heejung Seo-Reich (Religions, 2022)
This article gathered and analyzed the Daodejing (DDJ) translations in Korean that appeared after the liberation from Japan and classified them into four perspectives: the perspective continuing Gyeonghak 經學 (Traditional Confucian exegetics), the literary and linguistic perspective, the religious perspective, and the philosophical perspective according to the academic perspective and methodology of translation. Simultaneously, this paper clarified the translation characteristics by comprehensively examining the formation process of each perspective in their historical contexts. Although Daoism had been excluded from the academic curriculum during the pre-liberation era along with Buddhism as heresy, it was later hastily embraced within the category of Oriental Studies to build a cultural consensus when the modern and contemporary educational system was established. In the post-liberation era, the formation of each DDJ translation perspective is directly related to the academic status of Daoism during the modernization of the Korean educational system—a process in which the years 1990 and 2015 stand out as essential turning points. The characteristics of DDJ translations in Korean can be analyzed from five perspectives depending on the Ur-text, ideological perspective, linguistic methodology, national characteristics, and relation to Christianity.